Cold agglutinin syndrome as a complication of Covid-19 in two cases. (October 2020) - Jensen, Christopher E.; Wilson, Samuel; Thombare, Aparna; Weiss, Susan; Ma, Alice
Abstract: Background: Cold agglutinins are autoantibodies against RBC antigens, leading to hemolysis at less-than-physiological temperatures through complement fixation. Production can be triggered by infections, resulting in secondary cold agglutinin syndrome (CAS). This syndrome has been classically described in the setting of Mycoplasma pneumoniae infection, as well as with several viral pathogens. Cases: Here, we present two cases of cold agglutinins identified in the context of Covid-19 in critically ill patients treated at our institution. Each case was characterized by little in - vivo hemolysis, but these antibodies complicated laboratory assessment and renal replacement therapy. Management included anticoagulation and warming of dialysis circuit. Conclusions: Despite minimal in - vivo hemolysis, these antibodies are of clinical significance given their implications for laboratory assessment and renal replacement therapy, particularly with the frequency of multi-organ system dysfunction associated with severe Covid-19. Highlights: Cold agglutinins are autoantibodies to RBCs that drive hemolysis at sub-physiologic temperatures via complement fixation. Cold agglutinin syndrome (CAS) has been recently reported in the setting of Covid-19. We present two cases of cold agglutinins identified in the context of Covid-19. Presence correlated with dialysis circuit failure, which was managed with anticoagulation and warming of circuit.